THE ASPECTS OF HINDUISM IN POE’S TALES, “LIGEIA” AND “MORELLA”: A STUDY OF REINCARNATION - Sumayah Sumayah (Universitas Sebelas Maret, 2023)
This study is an attempt to discuss (1) what Hinduism is. (2) what the concept of reincarnation is.(3) what aspects of Hinduism reflected in Poe’s tales “Ligeia” and “Morella”. This study used American Studies theory that is the reconciliation of time (past, present, future), of space and of academic disciplines that are philosophical, historical, and literary approaches. The literary approach used, in this case, is the expressive one. The method applied in this study is analytical descriptive that utilizes library research and concentrates the attention on reference sources related to the topic discussed. The Result of the study shows that there are the aspects of Hinduism namely the wandering spirit and the reincarnation. In Poe’s tales, “Ligeia” and “Morella” the wandering spirit happens when they died. Ligeia, the main character reincarnate into Rowena and Rowena becomes Ligeia again. Morella reincarnates into her baby, Morella. It is the same name.